2014
DOI: 10.1177/2325957414557267
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Perspectives on Delaying Initiation of Antiretroviral Therapy for Clinically Eligible HIV-Infected Patients

Abstract: Objectives:Guidelines for antiretroviral therapy (ART) initiation have evolved, but consistently note that adherence problems should be considered and addressed. Little is known regarding the reasons providers delay ART initiation in clinically eligible patients.Methods:In 2009, we surveyed a probability sample of HIV care providers in 582 outpatient facilities in the United States and Puerto Rico with an open-ended question about nonclinical reasons for delaying ART initiation in otherwise clinically eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 37 publications
2
52
0
Order By: Relevance
“…Retention in care and HIV disparities research have been linked through numerous studies describing the relationship between clinical engagement, access to and initiation of therapy, continuity of care, and viral suppression and other markers of HIV disease progression in various populations and settings, both in resource-rich and resource-limited settings. 12,13,15,16,18,[29][30][31] In fact, the relationship between retention disparities and lack of viral suppression alone merits close attention as viral suppression is a priority outcome in the NHAS, implicating improved individual outcomes and reduced HIV transmission. 5,8,[29][30][31] Few studies, however, have followed a cohort as large as the NA-ACCORD population over such a long period of time after ART initiation, a long enough period to directly observe the median times of first discontinuity of retention in care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retention in care and HIV disparities research have been linked through numerous studies describing the relationship between clinical engagement, access to and initiation of therapy, continuity of care, and viral suppression and other markers of HIV disease progression in various populations and settings, both in resource-rich and resource-limited settings. 12,13,15,16,18,[29][30][31] In fact, the relationship between retention disparities and lack of viral suppression alone merits close attention as viral suppression is a priority outcome in the NHAS, implicating improved individual outcomes and reduced HIV transmission. 5,8,[29][30][31] Few studies, however, have followed a cohort as large as the NA-ACCORD population over such a long period of time after ART initiation, a long enough period to directly observe the median times of first discontinuity of retention in care.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] However, studies examining sex differences in retention or interruption of therapy have been limited in the generalizability of their findings due to being performed in the context of clinical trials, in resourcelimited settings, or at single clinical sites. [17][18][19][20] Where racial and HIV risk disparities in retention and HIV outcomes are concerned, many of the aforementioned studies have also noted significant differences for persons of black race and those with injection drug use (IDU), 4,5,9,12,14,16 although at least one clinical cohort has noted a resolution of racial disparities in HIV outcomes in its recent history. 21 These studies have also been limited by lack of information on ART use or have used different methods to adjust for the ART status of their participants while examining retention outcomes.…”
mentioning
confidence: 99%
“…Other studies have suggested that individual ART acceptance is an important determinant of initial ART prescription and utilization [15]. Many structural barriers to ART utilization are removed in the prison setting, yet others, which are unique to prisons, including violence and hopelessness, can discourage ART utilization [13, 47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Prisoners living with HIV are often people who inject drugs (PWID) who are incarcerated due to criminalization of drug use under Indonesian law. Although the structured prison setting offers opportunities to improve ART access and utilization [1012], numerous individual and institutional factors may contribute to ART being delayed, declined, or discontinued in clinically eligible PLH, including a patient’s trust in physicians [13], belief in the personal necessity of ART [14], or readiness to commit to ART [15]. Prison overcrowding, opportunistic infections, and delayed ART initiation contribute to high HIV-related mortality in Indonesian prisons [16–18].…”
Section: Introductionmentioning
confidence: 99%
“…41 Finally, we did not have available data on some patient-level risk factors for delayed cART start or adherence to care and cART, such as depression or alcohol dependence, or structural and socioeconomic factors as income, housing instability, or stigma and discrimination that could interfere with achieving optimal outcomes. 17,19,42 In conclusion, we found that over a 13.5-year period (2000-2013), although the CD4 count at HIV diagnosis has not improved significantly among enrollees in the HOPS, the timeliness of initiation of cART and subsequent VS have both improved. However, heterosexual men were diagnosed at significantly lower CD4 counts than all other subgroups.…”
Section: Discussionmentioning
confidence: 61%